The Influence of Product Features, Customer Testimonials, and Brand Image on Purchase Intention of Smartphones at Erafone Palembang Square - Erpin, Erpin; Setiawan, Budi; Veronica, Meilin (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study aims to determine the effect of product features, customer testimonials, and brand image on the purchase intention of smartphones at Erafone Palembang Square, both partially and simultaneously. This research employed a quantitative method with an associative approach. The population consisted of all consumers of Erafone Palembang Square totaling 1,100 people, with a sample of 293 respondents determined using the Slovin formula and purposive sampling technique. Data were collected through questionnaires and analyzed using multiple linear regression with the assistance of SPSS version 26. The partial test (t-test) results showed that all three independent variables product features, customer testimonials, and brand image had a positive and significant effect on purchase intention. The simultaneous test (F-test) also indicated that these variables collectively had a significant influence on purchase intention for smartphones. These findings suggest that improving product features, providing convincing customer testimonials, and strengthening brand image can serve as effective strategies to increase consumer purchase intention Keywords: Product Features, Customer Testimonials, Brand Image, Purchase Intention, Smartphone.